Vegetation as a Resource: Characterization and Management in the Moist Savannas of Africa - Isichei, A. O.; Akobundu, I. O. (2014)
Savannas cover up to 65% of Africa's land area and up to 80% of West Africa and occur between the equatorial rainforests and mid-latitude deserts. They have a continuous C4 grass stratum at least 80 cm high with fit, cauline leaves; trees and shrubs are often present and the vegetation is usually burnt annually, especially in the moist areas. Climate has been the major criterion used for zoning savannas but the structure of the vegetation and floristic composition, geology and geomorphology have also been med. There have been continental sale classifications of savanna, most prominent of which are those of AETFAT, which recognizes twelve savanna formations in Africa; and of UNESCO/AETFAT/UNESCO, more recent, and partially based on that of AETFAT. There are several regional classifications including that of Keay for Nigeria whose nomenclature is now widely wed in West Africa Moist savannas are found in low altitude (< 800 m above sea level) Western and Central Africa, in the ecoclimatic zone where the moisture indexed length of the growing season is between 151 and 270 days and where the annual rainfall/evapotranspiration ratio is between 0.40 and 1.0. Moist savannas are mainly woodlands and range from Isoberlinia woodlands to forest-savanna transition zones where oil palm, characteristic of secondary forest vegetation, is common. Moist savanna vegetation plays an important role in nutrient cycling, first through lifter deposition and decay, from which soil organic matter is built up. Rhizobia and other micro-organism symbiotic and non-symbiotic associations with plants also fix atmospheric nitrogen. Some plants also have mycorrhiza which aid in nutrient absorption from the soil. Many savanna plants play secondary roles in agriculture, providing poles for fences and stakes for yam. Cultivation presents a major perturbation to the natural resilience of the moist savannas; land use should therefore ensure that the natural resiliency of the ecosystem is maintained.